Meniscal Regenerative Scaffolds Based on Biopolymers and Polymers: Recent Status and Applications - Li, Hao; Li, Pinxue; Yang, Zhen; Gao, Cangjian; Fu, Liwei; Liao, Zhiyao; Zhao, Tianyuan; Cao, Fuyang; Chen, Wei; Peng, Yu; Yuan, Zhiguo; Sui, Xiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
The knee menisci are structurally complex components that preserve appropriate biomechanics of the knee. Meniscal tissue is susceptible to injury and cannot heal spontaneously from most pathologies, especially considering the limited regenerative capacity of the inner avascular region. Conventional clinical treatments span from conservative therapy to meniscus implantation, all with limitations. There have been advances in meniscus tissue engineering and regenerative medicine in terms of potential combinations of polymeric biomaterials, endogenous cells and stimuli, resulting in innovative strategies. Recently, polymeric scaffolds have been utilized to rationally support the requirements for meniscal tissue regeneration, ranging from an ideal architecture to biocompatibility and bioactivity. Additionally, multiple challenges involving the anisotropic structure and sophisticated regenerative process of the meniscus still create barriers to clinical application. Considering the advances of three-dimensional printing in tissue engineering, polymeric scaffolds fabricated by this technology are alternative strategies, and some studies have shed light on this field. Accordingly, this review aims to summarize the state of the art of current polymers used to fabricate meniscal scaffolds and their applications in vivo and in vitro to evaluate their potential utility in meniscus tissue engineering. Combinations of natural and synthetic polymers are described, with a focus on advanced strategies associated with improvements in scaffold manufacturing technology. Ideal meniscal implants with an appropriate macro/microarchitecture, bioactivity and orchestrated degradation are required in the future.